Exploring the Application of Blockchain Technology in the Supply Chain of the Automotive Industry - Radhakrishnan, Kuttupuzha Siddharth; Shafighi, Najla; Hajibashi, Anahita Amini (Archives of Business Research, 2024)
The purpose of this study is to assess the impact of blockchain technology in the supply chain of the automotive industry and its effect on supply chain efficiency. A quantitative approach has been used by a self-administered questionnaire among 100 supply chain professionals predominantly from the automotive industry and to the blockchain professionals in other industries in Europe. The result of the investigation showed that there is enhancement of supply chain efficiency by the implementation of blockchain in the supply chain of the Automotive industry. In addition, based on the regression and correlation analysis, it concluded that data transparency, traceability, security of the data are significantly correlated with supply chain efficiency of the organization when blockchain technology is implemented. The study also examines the cost of implementation of blockchain technology which influences the decision-making process of adoption of blockchain technology for supply chain efficiency.